PENGARUH INTENSITAS CAHAYA DAN DOSIS PUPUK UREA TERHADAP PERTUMBUHAN BIBIT JAMBU METE (Anacardium occidentale L.) - Risman, Risman; Muslimin, muslimin; Taiyeb, asgar (Universitas Tadulako, 2020)
(Anacardium occidentale L.) is a conservation plant and its development in Indonesia has been started since 1975 through the Ministry of Forestry's project as a conservation plant to repair critical land. The study was conducted for three months, starting from March to May 2018. The research location was located in the nursery around the Forestry Science Laboratory of the Faculty of Forestry. This study uses a factorial Randomized Complete Design Method (RAL) consisting of two factors, namely the first factor of light intensity C1 = 30%, C2 = 50%, C3 = 70% and C4 = 100% and the second factor is the dose of Urea P0 = without Urea fertilizer, P1 = 1 g and P2 = 2 g per polybag. The combination of the two factors is 12 combinations and each treatment is repeated 4 times. The parameters observed included height increase, increase in diamater, increase in number of leaves and measurement of leaf area. The results of this study indicate that the treatment of Urea fertilizer dosage has a very significant effect on the increase in cashew nut seedlings aged 12 MST. The treatment of 2 g fertilizer dose gave a high increase of 2.0 cm which was significantly different from the treatment without fertilizer (P0) which was 1.4 cm. In addition, the treatment of light intensity and its interaction with Urea fertilizer has no significant effect on all observational parameters of age 12 MST. The treatment of 30% light intensity gave the best results for height increments of 2.0 cm and an increase in diameter of 0.82 mm at 12 MST. The interaction of light intensity and urea fertilizer (C1P2) tended to give the best effect on the parameters of high increase of 2.5 cm, the increase in diameter of 0.82 mm and the increase in the number of leaves of 2.4 strands aged 12 MST.Keywords: Light Intensity, Cashew Seed Urea Fertilizer (Anacardium Occidentale L).